Integrating Technology to Foster Critical Thinking Skills in Higher Education Courses: A Survey-Based Study of Lecturers Perceptions - Gunawan; Sahril; Abduh, Amirullah; Samtidar (Decode: Jurnal Pendidikan Teknologi Informasi, 2026)
This study examines lecturers’ perceptions of technology integration in fostering students’ critical thinking skills in higher education. Employing a quantitative approach with a survey research design, data were collected from 62 lecturers across various academic disciplines at Universitas Muhammadiyah Bone, Indonesia. A structured Likert-scale questionnaire was used to capture lecturers’ perceptions across three dimensions: personal attitudes, pedagogical understanding, and teaching experience related to technology-supported critical thinking instruction. The data were analysed using descriptive statistics, including frequencies and percentages, with the aid of SPSS for windows (IBSM SPSS statistic 28.0). The findings indicate that lecturers generally demonstrate positive attitudes and high awareness regarding the importance of critical thinking as a core learning outcome in higher education, and they perceive technology as a valuable pedagogical tool for supporting analysis, evaluation, evidence-based argumentation, and metacognitive reflection. Lecturers also reported a relatively strong conceptual understanding of critical thinking frameworks and technology integration principles. However, the results reveal a noticeable gap between lecturers’ perceived readiness and the consistent implementation of complex, technology-based argumentative learning practices. Additionally, perceived challenges related to infrastructure limitations, institutional support, and pedagogical training were identified. This study highlights the need for structured instructional design frameworks and sustained institutional support to translate positive perceptions into effective pedagogical practice. The findings contribute insight into lecturers’ perceptions and inform future efforts to enhance technology-supported critical thinking in higher education.